2011
DOI: 10.1038/ajh.2010.236
|View full text |Cite
|
Sign up to set email alerts
|

Higher Blood Pressure Associated With Higher Cognition and Functionality Among Centenarians in Australia

Abstract: Centenarians have a very low prevalence of high BP and high cholesterol compared with the general population. There seems to be an inverse relationship between the risk factors for cardiovascular disease vs. the risk factors for dementia in our sample. There appears to be a complex interaction between BP and health in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 24 publications
3
39
0
6
Order By: Relevance
“…In support of this hypothesis, individuals with lower cerebral blood flow have been found to have higher rates of cognitive decline [27] and prevalent dementia [28]. If increased BP is a compensatory mechanism, it would also help maintain adequate perfusion in other vital organs [29] and may explain the protective associations between increased BP and other outcomes such as mortality [30], frailty indicators [31], disability [32], and physical decline [33] in the very elderly.…”
Section: Discussionmentioning
confidence: 66%
“…In support of this hypothesis, individuals with lower cerebral blood flow have been found to have higher rates of cognitive decline [27] and prevalent dementia [28]. If increased BP is a compensatory mechanism, it would also help maintain adequate perfusion in other vital organs [29] and may explain the protective associations between increased BP and other outcomes such as mortality [30], frailty indicators [31], disability [32], and physical decline [33] in the very elderly.…”
Section: Discussionmentioning
confidence: 66%
“…Cross-sectional studies in older individuals have demonstrated a relation between high BP and poor physical function and physical disability as defined by lower gait speed, difficulty with activities of daily living, or reduced lower limb function. [61][62][63] Results of longitudinal studies later in life are, however, inconsistent; in well-functioning older persons aged 70 to 80 years, high BP was related to physical decline (gait slowing) 61,64 and disability, 65 whereas in the oldest old low BP was related to physical decline 56,66 and lower grip strength. 67 Combined with systematic reviews from a life-course perspective reporting on the relation between BP and functioning, 51,68 these findings suggest an age-dependent association of BP with risk of functional impairment: midlife hypertension causes cognitive and physical limitations later in life, but this relation seems to be inverted in certain subgroups of (biologically) older individuals.…”
Section: Risk Of Functional Disabilitiesmentioning
confidence: 99%
“…For studies focused on the very elderly, most studies rely on cross-sectional data [1921] and less sensitive measures of global cognition [2022]. Studies that looked at the relationship between blood pressure and cognitive performance in the very elderly found that a lower SBP was associated with greater cognitive dysfunction both cross-sectionally and longitudinally, while higher blood pressure was associated with better cognitive performance [2022], however, these studies relied on HTN measures acquired at old age and a single composite cognitive score.…”
Section: Introductionmentioning
confidence: 99%